Penerapan Model Pembelajaran Kooperatif Tipe Scramble Berbantuan Media Couple Card (CORD) terhadap Motivasi Belajar Sejarah - Adhima*, Faudhan; Zulfan, Zulfan; Haikal, Muhammad (Universitas Syiah Kuala, 2024)
This research aims to determine the application of the scramble model assisted by couple card media in history learning in class X IPS MAN 2 Bireuen and to determine the learning motivation of class This researchuses a qualitative approach with descriptive research type. The subjects in this research were all students of class X IPS MAN 2 Bireuen, totaling 25 students. The data collection technique in this research uses observation and questionnaires. Based on the results of the research that has been carried out, it is known that (1) the results of observing teacher and student activities in the implementation of learning are 95.5% in the very good category. (2) Students' motivation towards the scramble model assisted by couple card media in history learning in class X IPS MAN 2 Bireuen that i 44.75% answered strongly agree, 22.5% answered agree, 13.25% answered disagree, and 19.5% answered strongly disagree with the very goodcategory. So it can be concluded that in the process of implementing the scramble model assistedby couple card media, it canincrease motivationto learn history.